2020
DOI: 10.4082/kjfm.18.0112
|View full text |Cite
|
Sign up to set email alerts
|

Association between Falls and Nutritional Status of Community-Dwelling Elderly People in Korea

Abstract: Background: Malnutrition is a well-known risk factor of falls, although studies examining the association between nutritional status and falls are rare. We aimed to investigate the association between nutritional status and falls according to gender among Korean older adults. Methods: The study included 10,675 participants (4,605 men and 6,070 women) aged 65 years and older and used data from the 2011 Survey of Living Conditions and Welfare Needs of Korean Older Persons. Nutritional status of the participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Searching five electronic databases yielded a total of 15,266 unique articles after the removal of duplicates. We reviewed 561 full‐text articles for eligibility and 74 articles were included in this scoping review 13,23–95 . The majority of the articles were excluded because their aim statements did not specifically mention falls, sex, and/or gender (see supplemental Tables S2 and S3 for the list of included and excluded studies, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Searching five electronic databases yielded a total of 15,266 unique articles after the removal of duplicates. We reviewed 561 full‐text articles for eligibility and 74 articles were included in this scoping review 13,23–95 . The majority of the articles were excluded because their aim statements did not specifically mention falls, sex, and/or gender (see supplemental Tables S2 and S3 for the list of included and excluded studies, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, female older adults were also more prone to experience fall incidents than male older adults using data from the Survey of Living Conditions and Welfare Needs of Korean Older Persons (OR 1.90 (95% CI 1.61 to 2.24)) for older women versus older men (OR 1.59 (95% CI 1.26 to 1.99)). The biological plausibility linking sex and falling may be related to sex-based differences in psychosocial aspects and bone and muscle balance due to ageing, as well as hormonal changes associated with menopause 30…”
Section: Discussionmentioning
confidence: 99%
“…The biological plausibility linking sex and falling may be related to sex-based differences in psychosocial aspects and bone and muscle balance due to ageing, as well as hormonal changes associated with menopause. 30 …”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with that of a previous meta-analysis that addressed the relationship between depression and falls (Kamińska et al, 2015). However, another study reported no association between depression and falls when depression was included in a multivariate analysis alongside physical functioning (Jo et al, 2020). Regarding the low OR s of depression and its nonsignificant association in the male old–old group in the multivariate analysis, the influence of depression on falls may have been more attenuated by age and gender in the study population.…”
Section: Discussionmentioning
confidence: 99%